MEDIASI PENAL DALAM PENANGANAN PELAKU TINDAK PIDANA SEBAGAI UPAYA MEMINIMALISIR KELEBIHAN HUNIAN DI LEMBAGA PEMASYARAKATAN - July Esther; Bintang ME Naibaho; Bintang Christine (Nommensen Journal of Legal Opinion, 2020)
The excess housing in the Indonesian Correctional Institution does not abate. This condition is faced with criminal efforts which should be a final diversion related to the effort to include convicted persons in Corrections Institutions. The aim is to analyze whether the mediation of penal as the application of Restorative Justice can be an alternative effort to minimize excess occupancy inmates in correctional institutions. The use of this research as a recommendation for law enforcement officials in the handling of criminal acts by promoting penal mediation. The research uses normative legal research methods with literature studies. Mediation Penal is considered able to be an intermediary process of mediation or peace between perpetrators of criminal acts with victims of criminal acts as minimizing the excess occupancy that starts from handling the police and prosecutors stage.